Accounting Practices and Organizational Performance: Evidence from Small and Medium Scale Enterprises in Sri Lanka - Balagobei, Saseela (Indian Journal of Finance and Banking, 2020)
Over the past few decades, the researchers demonstrate consistent effort in investigating the Small and Medium scale Enterprises (SMEs). This sector plays a crucial role in the economic growth in both developing and developed countries. The research investigated how accounting practices influence the organizational performance of small and medium scale enterprises in Sri Lanka. Accounting practices consists of record keeping, budgeting practices and payroll accounting whereas organizational performance is measured by organizational goal achievement, organizational effectiveness and organizational efficiency records. A structured questionnaire was used to collect the primary data from 75 SMEs which were selected by means of the random sampling technique. The results revealed that among the accounting practices, only record keeping and budgeting practices have significant positive influence on organizational performance of Small and medium enterprises in Sri Lanka. It can be recommended that academic institutions and other bodies which are responsible for SMEs should organize training programmes for those operators who do not have the technical knowhow in the field of accounting to come to grips with it and also provide some SME-specific accounting guidelines and template forms for capturing accounting practices for the operators to use.JEL Classification: M41.